Cryptanalysis of Critical Security Mechanism designed for Hierarchical Multi-medical Server in TMIS Environment - B Rama Subba Reddy, Dr.; V L N SUJITH, A. (International Journal of Engineering and Technology, 2018)
The rapid advancement of pervasive computing, nano-technology and wearable systems, given rise to low-power internet based systems in elimination of distance complications by application of â€˜The telecare medicine information system (TMIS)â€™, which consists of sensor, medical server and physician servers to sense human biological readings and monitor the health condition of the patients. Due to the association of patient crucial data, and transferring it over an insecure and public communication channel, there is a critical prerequisite for patient authentication, data integrity and data privacy. In this context many researchers had proposed various schemes for user authentication and secure data transmission over TMIS. Recently A.K.Das et al proposed a three-factor user authentication and key agreement protocol for TMIS and claimed that the proposed protocol is efficient, secure and lightweight. We review their scheme for resistance to well-known cryptographic attacks. Though A.K.Das et al scheme resists major cryptographic attacks, after in-depth analysis, we demonstrate that their scheme has security pitfalls such as failure to resist replay attack, known session-specific temporary information attack,and failure to resist stolen-verifier attack.Â Â